Exhaled nitric oxide detection for diagnosis of COVID-19 in critically ill patients - Matthew C. Exline (Public Library of Science (PLoS), 2021)
Background COVID-19 may present with a variety of clinical syndromes, however, the upper airway and the lower respiratory tract are the principle sites of infection. Previous work on respiratory viral infections demonstrated that airway inflammation results in the release of volatile organic compounds as well as nitric oxide. The detection of these gases from patients’ exhaled breath offers a novel potential diagnostic target for COVID-19 that would offer real-time screening of patients for COVID-19 infection. Methods and findings We present here a breath tester utilizing a catalytically active material, which allows for the temporal manifestation of the gaseous biomarkers’ interactions with the sensor, thus giving a distinct breath print of the disease. A total of 46 Intensive Care Unit (ICU) patients on mechanical ventilation participated in the study, 23 with active COVID-19 respiratory infection and 23 non-COVID-19 controls. Exhaled breath bags were collected on ICU days 1, 3, 7, and 10 or until liberation from mechanical ventilation. The breathalyzer detected high exhaled nitric oxide (NO) concentration with a distinctive pattern for patients with active COVID-19 pneumonia. The COVID-19 “breath print” has the pattern of the small Greek letter omega (). The “breath print” identified patients with COVID-19 pneumonia with 88% accuracy upon their admission to the ICU. Furthermore, the sensitivity index of the breath print (which scales with the concentration of the key biomarker ammonia) appears to correlate with duration of COVID-19 infection. Conclusions The implication of this breath tester technology for the rapid screening for COVID-19 and potentially detection of other infectious diseases in the future.